Radiological assessment of flour consumed in Kuwait - Alrefae, Tareq; Nageswaran, Tiruvachi N.; Alshemaly, Taher; Demir, Nasser (Kuwait Journal of Science, 2018)
This study investigated the natural radioactivity in flour consumed in Kuwait. To cover a wide range of samples, wheat, rice and gram (chickpeas) based flour samples were tested. Gamma spectrometry revealed the presence of 226Ra, and 40K in all samples, while 228Ra was detected in 14 out of the 18 samples. The activity concentrations of the three radionuclides were found to be within the normal levels, and hence so did the estimated annual effective doses. Moreover, the estimated lifetime cancer risk was found to be well below the acceptable level. Hence, these findings confirm the radiological safety of flour consumed in Kuwait for the three targeted radionuclides. Interestingly, statistical significant differences were found in the averages of the activity concentrations that were sensitive to the ingredient of the flour.